Analysis of urine composition from split 24-h samples: use of 12-h overnight samples to evaluate risk factors for calcium stones in healthy and stone-forming children. Issue 3 (June 2020) - Mir, Concepcion; Rodriguez, Adrian; Rodrigo, Dolores; Saez-Torres, Concepcion; Frontera, Guiem; Lumbreras, Javier; Espinosa, Natalia; Gomez, Cristina; Costa-Bauza, Antonia; Grases, Felix
Summary: Introduction: The analysis of 24-h urine is the gold standard to diagnose metabolic abnormalities in the stone-forming patient. However, urinary composition changes throughout the day and analyzing the whole 24-h urine may mask peaks of increased risk of crystallization. Objective: To examine variations of stone-promoting and stone-inhibiting factors in urine using split 24-h samples from healthy and stone-forming children. Study design: Urine was collected from 87 healthy and 26 stone-forming children using a split collection procedure (12-h daytime urine and 12-h overnight urine). Urine volume, pH, calcium (Ca), magnesium (Mg), phosphate (P), citrate (Cit), uric acid (Ur), and oxalate (Ox) were determined, and the Ca/Cit ratio was calculated. Results: The overnight urine samples in both groups had higher levels of P and Mg, lower volume, lower pH, and less citrate and uric acid. As can be seen in the table, higher percentages of healthy and stone-forming children had altered 12-h night urine than 24-h urine with regards to Ca/Cr, Cit/Cr and Ca/Cit ratios. All healthy subjects and all stone-forming children (except one) with altered Cit/Cr ratios or Ca/Cit ratios in the 24-h sample also had altered ratios in the 12-h overnight sample. Discussion: This study indicates that urine composition changes throughout the day, and that there is daily variability in most of the parameters related to kidney stone formation. Furthermore, 12-h overnight samples seem to be more sensitive than 24-h samples in detecting the most common urinary abnormalities. The main limitation of this study is the relative low sample size of stone-forming children, owing to the low prevalence of nephrolithiasis in childhood. Conclusions: We observed a higher excretion of stone-promoting substances and a lower citrate in urine at night. However, the study results do not provide enough evidence to conclude that the use of a 12-h overnight sample collection can replace 24 h urine analysis in the metabolic evaluation of children with lithiasis. Summary Table Number (percentage) of urine samples with Ca/Cr, Cit/Cr, and Ca/Cit above cut points of normal. Table Urinary alteration Healthy Stone formers 12-h night urine 24-h urine 12-h night urine 24-h urine Ca/Cr > 0.20 mg/mg 6/87 (6.9%) 1/87 (1.1%) 8/26 (30.8%) 10/26 (38%) Cit/Cr < 250 mg/g 15/87 (17.2%) 4/87 (4.6%) 9/26 (34.6%) 5/26 (19.2%) Ca/Cit > 0.33 mg/mg 22/87 (25%) 7/87 (8%) 21/26 (80.8%) 18/26 (69.2%)